1990
DOI: 10.1007/bf01906964
|View full text |Cite
|
Sign up to set email alerts
|

Physiological hypotheses-Intramyocardial pressure. A new concept, suggestions for measurement

Abstract: Intramyocardial pressure is supposed to play a major role in systolic coronary flow impediment. Via its assumed relation with radial wall stress it is supposed to be similar to ventricular pressure at the endocardium and decreases linearly to negligible values epicardially. Many attempts to measure intramyocardial pressure have been reported in the literature with rather different results. For instance, with most of the various methods, intramyocardial pressures both higher and lower than left ventricular pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 67 publications
4
31
0
Order By: Relevance
“…In general, the reported results are somewhat inconsistent and appear to depend on measurement technique. As Westerhof (22) summarizes, some authors have found subendocardial IMP higher than VP, whereas others have found IMP to be lower than peak systolic VP (5). Most groups, however, agree that IMP decreases relatively smoothly from endocardium to epicardium, as suggested by some theoretical models (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the reported results are somewhat inconsistent and appear to depend on measurement technique. As Westerhof (22) summarizes, some authors have found subendocardial IMP higher than VP, whereas others have found IMP to be lower than peak systolic VP (5). Most groups, however, agree that IMP decreases relatively smoothly from endocardium to epicardium, as suggested by some theoretical models (22).…”
Section: Discussionmentioning
confidence: 99%
“…As Westerhof (22) summarizes, some authors have found subendocardial IMP higher than VP, whereas others have found IMP to be lower than peak systolic VP (5). Most groups, however, agree that IMP decreases relatively smoothly from endocardium to epicardium, as suggested by some theoretical models (22). This distribution may be related to the greater stress and strain predicted by models for the subendocardial layers (26).…”
Section: Discussionmentioning
confidence: 99%
“…A minimal model should contain a representation of the relationships between inflow pressures, ventricular pressures and outflow pressures. An example is the cyclical elastance model of the heart [2], a remarkably simple model adequate to give reasonable approximations to the pressure waveforms in the ventricle and aorta, and reasonable stroke volumes, and even reasonable durations of transients in response to changes in state.…”
Section: Models Of the Cardionomementioning
confidence: 99%
“…In the venous compartment no valves are present, thus an increase in developed venous pressure leads instantaneously to a decrease in venous volume. However, if the end-diastolic volume increases, as indicated by the arrow along the diastolic pressure-volume curve (for instance by prolongation of diastole), systolic venous pressure will be increased in the following systole, depending on the amount of volume displaced, irrespective of the developed left ventricular pressure (figure modified from Westerhof, 1990). A change in inotropic state of the ventricle will affect the venous pressure pulse by changing the slope of the end-systolic elastance relation.…”
Section: Statistical Testsmentioning
confidence: 99%
“…An alternative hypothesis to explain pressure generation in intramyocardial vessels put forward by Krams et al (1989) and Westerhof (1990) predicts that the pressure in the intramyocardial vessels depends on cyclical elastance variations and vascular volume (see Introduction). As is illustrated in Fig.…”
Section: Generation Of Pressure Pulses In Intramyocardial Veinsmentioning
confidence: 99%